Impact of genotypic diversity on selection of subtype-specific drug resistance profiles during raltegravir-based therapy in individuals infected with B and BF recombinant HIV-1 strains. (3rd March 2020) - Sánchez, Daniela; Arazi Caillaud, Solange; Zapiola, Ines; Fernandez Giuliano, Silvina; Bologna, Rosa; Mangano, Andrea; Aulicino, Paula C
Abstract: Background: Current knowledge on HIV-1 resistance to integrase inhibitors (INIs) is based mostly on subtype B strains. This contrasts with the increasing use of INIs in low- and middle-income countries, where non-B subtypes predominate. Materials and methods: HIV-1 drug resistance genotyping was performed in 30 HIV-1-infected individuals undergoing virological failure to raltegravir. Drug resistance mutations (DRMs) and HIV-1 subtype were characterized using Stanford HIVdb and phylogenetic analyses. Results: Of the 30 integrase (IN) sequences, 14 were characterized as subtype F (47%), 8 as subtype B (27%), 7 as BF recombinants (23%) and 1 as a putative CRF05_DF (3%). In 25 cases (83%), protease and reverse transcriptase (PR-RT) sequences from the same individuals confirmed the presence of different BF recombinants. Stanford HIVdb genotyping was concordant with phylogenetic inference in 70% of IN and 60% of PR-RT sequences. INI DRMs differed between B and F IN subtypes, with Q148K/R/H, G140S and E138K/A being more prevalent in subtype B (63% versus 0%, P = 0.0021; 50% versus 0%, P = 0.0096; and 50% versus 0%, P = 0.0096, respectively). These differences were independent of the time on raltegravir therapy or viral load at the time of genotyping. INI DRMs in subtype F IN genomes predicted a lower level of resistance to raltegravir and no cross-resistance to second-generation INIs. Conclusions: Alternative resistance pathways to raltegravir develop in subtypes B and F IN genomes, with implications for clinical practice. Evaluating the role of HIV-1 subtype in development and persistence of mutations that confer resistance to INIs will be important to improve algorithms for resistance testing and optimize the use of INIs.